(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The radiosensitivity of the eggs of Epichoristodes acerbella (Walk.) has been investigated in order to use ionizing radiations for treating infested cut carnations. Doses from 5 to 70 krad have been applied to the eggs at 7, 4 and 1 day before hatching. The main results achieved have shown: - the doses of 7, 20 and 70 krad respectively applied on eggs of 2, 5 and 8 days of age caused a mortality of 100%; - a dose of 13 krad on old eggs is sufficient to kill all insects in the crysalid stage; - a dose of 10 krad induced a complete sterility of the adults obtained from treated eggs.